1988
DOI: 10.1902/jop.1988.59.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Initial Wound Healing Attachments to Demineralized Dentin

Abstract: This report describes the initial in vivo wound healing response of connective tissue components and cells to demineralized and nondemineralized dentin surfaces. Rectangular dentin specimens were prepared from beneath root surfaces covered by periodontal ligament. One group of six specimens were treated with citric acid, while another six specimens served as untreated controls. Specimens were implanted vertically into the skin of rats such that one end of the implant protruded above the skin. After one day, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…A significant difference was found in the presence of the smear layer between ultrasonic scaling and laser treatments. 22 It is important to determine how long the smear layer remains on the root surface after scaling and root planing as it may interfere with the biological events involved in the regeneration of periodontal tissues, 1,12,23 particularly in the early phases of healing. The smear layer, which is interposed between the root and the tissues, can prevent blood clot adhesion and cell attachment to the root surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant difference was found in the presence of the smear layer between ultrasonic scaling and laser treatments. 22 It is important to determine how long the smear layer remains on the root surface after scaling and root planing as it may interfere with the biological events involved in the regeneration of periodontal tissues, 1,12,23 particularly in the early phases of healing. The smear layer, which is interposed between the root and the tissues, can prevent blood clot adhesion and cell attachment to the root surface.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The cellular responses to demineralized and nondemineralized dentin were studied in a subcutaneous transfixation model in rodents, and an improved response was reported in the demineralized samples, which present a surface that is similar to smear layerfree dentin compared to the nondemineralized dentin samples in which the surface is similar to smear layercovered dentin. 23 In addition, fibrin linkage to exposed collagen fibrils on etched root surfaces prevents the apical migration of the epithelium and precedes collagen fiber attachment to the root surfaces. 5 Several animal studies have shown favorable results of regenerative therapies that are associated with chemical root surface conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…32 The physical properties of dentin surface contribute to the cell response too, and demineralized dentin predisposed toward cell attachment and oriented fiber attachment could develop on the demineralized dentin surface, which was structurally similar to PDL. 33,34 Many people extract healthy teeth for reasons such as impaction and treatment need, and stem cells, including PDLSCs and DPSCs, have been identified from these teeth. [2][3][4] Based on the results obtained in this research, a possible method of restoring tooth loss could be proposed in which tooth pulp was tissue engineered with expanded DPSCs, and the shape and size of the tissue-engineered dentin is controlled with an inductive substrate; then cementum and PDL is bioengineered on the dentin surface to form tooth root.…”
Section: Discussionmentioning
confidence: 99%
“…[2], [3] It might act as a barrier, preventing blood clot adhesion to the root surface [1] and periodontal regeneration. [2] To overcome this problem root surface conditioning is done.…”
mentioning
confidence: 99%
“…[2], [3] It might act as a barrier, preventing blood clot adhesion to the root surface [1] and periodontal regeneration. [2] To overcome this problem root surface conditioning is done. It exposes the organic dental matrix rendering root surface more biocompatible, which may increase success in regenerative procedures by creating an appropriate surface for cell attachment and eventual development of fiber attachment.…”
mentioning
confidence: 99%